(untitled) (Al-Academy, 2022)
The research discussed the propositions of functional structures and the requirements for their transformation according to the variables of use and human interaction through the variables of functions with one form products، multifunctional variables، and transforming form in one product. The patterns of user’s interaction with products were discussed through the variables of functional type، starting from defining the types of functions in the industrial product structures to: practical functions، which were classified into: informational functions، ergonomic functions، use، handling، comfort، global، anthropometric adaptation and physical postures. While the interaction variables were discussed according to the meaning function based on the symbolic meaning that the user attributes to the product design، which were categorized into: cultural (relational)، social and personal (emotional). As well as the function of maintaining trust and social function، which has been categorized into: the relational function، the communication and identification function، the remembering function، the function stemming from the necessity of daily interaction، the economic function، the self-activation function، and the aesthetic function، which is determined by finding specific pleasures for the user، which are classified as follows: Physical pleasure، social pleasure، psychological pleasure and intellectual pleasure. The aesthetic function of the product can be analyzed according to elements of: shape، material، surface and color. And on the discussion of the variables of user interaction of the functional type، a number of conclusions were reached that were، in total، an objective analysis of the relationships of functions with each other and how the functional type was affected by the contexts and requirements of user interaction and the transformation of functional structures based on the necessities of physical، intellectual and emotional interaction، within the framework of Total user experience.